IKLAN LAYANAN KESEHATAN MASYARAKAT (ILKM): KAJIAN SEMIOTIK - I Made Suwitra; Nyoman Suarjana (Kajian Linguistik dan Sastra, 2020)
Public health service advertisements (PHSA) tend to provide information, remind, add value, influence, and even change people's attitudes to healthy living. The purpose of this study was to determine the style of language, meaning, and public health service advertising ideology. The results of this study showed that; (1) the Public Health Service Ads (PHSA) language style, (2) the diction or word choice used tends to be informal, general, brief and understandable by ordinary learned societies. Regarding the tone contained, the narrative text had a simple language style, usually suitable to give instructions, commands, lessons, lectures, and the like. From the meaning point of view, semiotic meaning came from the relation between signifier and signified or it was the meaning of connotation. The ideology that lied behind sourced from the resulting connotation. The way to express imperatively as well as the use of symbols, colors, backgrounds (sign) such as thermometers; for instance. This has determined that PHSA concerned with hygiene, health, precautions, caution, caring, togetherness, planning, prosperity, and happiness.Keywords: PHSA, language style, meaning, ideology